2001
DOI: 10.1097/00007632-200103010-00018
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver and Intraobserver Agreement of Radiograph Interpretation With and Without Pedicle Screw Implants

Abstract: It is extremely difficult to interpret radiographic lumbar posterolateral fusion success. Such an assessment needs to be performed by use of a detailed radiographic classification system. The classification system presented here revealed good interobserver and intraobserver agreement, both with and without instrumentation. The classification showed acceptable reliability and may be one way to improve interstudy and intrastudy correlation of radiologic outcomes after posterolateral spinal fusion. Instrumentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 15 publications
1
76
0
2
Order By: Relevance
“…However, these studies included multiple diagnostic groups, and clinical as well as radiological outcomes were not always reported. Standard radiographs were used to assess fusion, which has been shown to underestimate pseudarthrosis rates [3,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies included multiple diagnostic groups, and clinical as well as radiological outcomes were not always reported. Standard radiographs were used to assess fusion, which has been shown to underestimate pseudarthrosis rates [3,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Hardware makes assessment of bony fusion difficult with the use of plain roentgenograms only [15]. Because of these difficulties the authors of this study used oblique views, bending tests and CT scans that justified solid fusion in all patients and all fused segments.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of allografts and ceramics the interpretation of solid fusion seems to be difficult, particularly when hardware is added. In contrast, Christensen et al [15] compared non-instrumented lumbar fusion versus instrumented with Cotrel Dubousset (CD) instrumentation and reported similar interobserver and intraobserver agreement. In particular Christensen et al [15] reported in the CD group j values of 0.63 and 0.81 for interobserver and intraobserver agreement, respectively; while in the non-instrumented spines for the interobserver and intraobserver agreement the j values were 0.52 and 0.73, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations